Ligustrum japonicum Thunb. Fruits Exert Antiosteoporotic Properties in Bone Marrow-Derived Mesenchymal Stromal Cells via Regulation of Adipocyte and Osteoblast Differentiation - Jung Hwan Oh; Fatih Karadeniz; Jung Im Lee; Youngwan Seo; Chang-Suk Kong (Hindawi Limited, 2021)
Ligustrum japonicum fruits have been used as a part of traditional medicinal practices and supplements in Korea and Japan. It has been reported to possess various bioactivities, but its antiosteoporotic potential and active substances have not been reported yet. The present study followed an ALP activity and lipid accumulation-guided screening of L. japonicum fruits for antiosteoporotic compounds and isolated salidroside as an active compound. Antiosteoporotic effects of L. japonicum fruits and salidroside were examined in mesenchymal stromal cells by their ability to enhance osteoblast formation by increased ALP activity and osteogenic marker gene expression while suppressing adipogenesis by inhibition of lipid accumulation and adipocyte marker gene expressions. Results showed that salidroside was able to enhance osteoblast differentiation via Wnt/BMP signaling pathway overactivation and suppress the PPARγ-mediated adipocyte differentiation, both through the MAPK pathway. In conclusion, L. japonicum fruits were suggested to possess antiosteoporotic activities and to be a source of antiosteoporotic substances such as salidroside.